2021
DOI: 10.3920/jiff2020.0081
|View full text |Cite
|
Sign up to set email alerts
|

Chemical safety of black soldier fly larvae (Hermetia illucens), knowledge gaps and recommendations for future research: a critical review

Abstract: Black soldier fly larvae (Hermetia illucens) (BSFL) are a promising protein source for the feed industry. They can be used to convert organic waste into valuable biomass, and due to their chemical composition, they are a valuable ingredient for several industrial sectors. To use BSFL as a feed ingredient, their chemical safety must be guaranteed. The composition of their rearing substrate is one of the crucial factors for safety, since it might introduce safety risks by bioaccumulation of various (in)organic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 71 publications
1
22
0
1
Order By: Relevance
“…Instead, larvae fed with plant or broilerbased substrate showed higher content of Cr, Cu and Se [23,43]. Low concentration of Ni and Zn were found both in substrate and in larvae [43], and concentrations of As, Cd and Pb were found comparable to literature data [23,[43][44][45][46].…”
Section: Knowledge On Hermetia Illucenssupporting
confidence: 65%
See 1 more Smart Citation
“…Instead, larvae fed with plant or broilerbased substrate showed higher content of Cr, Cu and Se [23,43]. Low concentration of Ni and Zn were found both in substrate and in larvae [43], and concentrations of As, Cd and Pb were found comparable to literature data [23,[43][44][45][46].…”
Section: Knowledge On Hermetia Illucenssupporting
confidence: 65%
“…Since larvae could be farmed on different substrates, it has been demonstrated that in speci c conditions or growth stages, H. illucens could bioaccumulate Cr, Cu, Fe, Se, Sn, Zn, Cd and Pb while no accumulation happens for Al and As [23,43]. The similarity of cadmium to calcium makes it easily bioavailable in larvae, where it can cumulate in the exoskeleton, as it happens for chromium [44]. Non-essential elements could be found in different concentrations in feed according to its origin, for example seaweed is a source of As which is well known as contaminant [46].…”
Section: Knowledge On Hermetia Illucensmentioning
confidence: 99%
“…Although not discussed in this review, food safety must be considered when using insects for certain applications (e.g., food and feed), especially when they are produced on side streams. The insects’ feed might introduce safety risks by microbial contamination and accumulation of several compounds in the insects, such as toxic metals, mycotoxins and pesticides [ 132 , 133 ], etc. Although research has been conducted regarding this topic, knowledge gaps are still present, which is mainly the reason why the European Union currently does not allow the use of several side streams as insects substrate.…”
Section: Discussionmentioning
confidence: 99%
“…As the demand for animal feed sources rises, insects are increasingly considered as a sustainable protein rich feed source (Stamer, 2015;Vandeweyer et al, 2021;Wang and Shelomi, 2017). Black soldier fly larvae (Hermetia illucens L., Diptera: Stratiomyidae) are known for their interesting nutritional value for animals, growth potential on various organic waste streams, high bioconversion ratio and low environmental impact (Diener et al, 2009;Joosten et al, 2020;Lievens et al, 2021;Makkar et al, 2014;Oonincx et al, 2015). While in Europe, Regulation (EC) No 2017/893 (EC, 2017) allows the use of black soldier fly larvae (BSFL) in aquafeed, the use of processed larvae in ruminants and monogastric animals is still prohibited at this moment by the EU feed ban or Regulation (EC) No 999/2001 (EC, 2001).…”
Section: Introductionmentioning
confidence: 99%